The Essential Elements of US Foreign Policy (Tikrit Journal For Political Science, 2017)
American foreign policy bases on several main pillar structure and bases on some strong and complicated institutions, it will be prepared for the sake of American foreign policy’s objectives, and will be implemented. American foreign policy is well-known either for its constant, or for its changing, it moves between reticence and intervention. In one hand, American foreign policy falls under the influence of rational principles. On the other hand, it is the policy of power and making interests. This research pursues the key pillars of American foreign policy, including history, thought, intellectual pillars and also it concentrates on economic and military pillars. Regarding history, this study exposes how the principles of American presidents had influence on American foreign policy, such as the principles of James Monroe, Woodrow Wilson, Ronald Regan, and George Bush. Also, this research sheds light on the role of all the mentioned pillars on American national security strategy and how American policy is prepared and implemented. The aim of this study is to demonstrate that if we want to make an accurate reading for American foreign policy, we have to understand these main pillars, which this policy establishes upon them, and also indicate the pillar’s influential on the policy.
Keywords: • Soft Power • National Security • Diplomacy • International Alliances • Economic Sanctions • Human Rights